The influence of humic acid on metal(loid)s leaching in landfill leachate for enhancing landfill mining - Lee, Hyeyeon; Coulon, Frederic; Wagland, Stuart T. (Elsevier, 2023)
The aim of this study was to investigate the effect of different concentrations of humic acid on the recovery rate of metal(loid)s in landfill leachate. The study focused on the release of 12 selected metal(loid)s, including critical raw materials (CRM) in landfills that were less than five years old and those that were more than ten years old. The experimental setup involved using different concentrations of humic acid (w/v) (0 %, 0.1 %, and 0.5 %) at pH 4 and 6. The results of the study showed that humic acid was effective in releasing Al, Cr, Co, Ni, Cu, Zn, As, Cd, and Pb. On the other hand, an increase in humic acid concentration led to a decrease in the release of Li, Mn, and Hg. The immobilization of Li, Mn, and Hg was due to the coordination and adsorption of humic acid. The presence of humic acid accelerated the release of metal(loid)s by carboxylic acidity compared to the recovery rate of metal(loid)s in landfill leachate without humic acid. However, a higher concentration of humic acid did not always result in a stronger recovery rate. The recovery rate of metal(loid)s was related to the solubility and concentration of humic acid. These findings can inform the development of more efficient and environmentally-friendly methods of recovering metal(loid)s using humic acid as a leaching agent.
Keywords: Landfill; Metal recovery; pH; Humic acid; Sustainability